Analysis of the methylation status of the apomixis-specific region in Paspalum spp. suggests an epigenetic control on parthenogenesis - Podio, Maricel (2014)
Apomixis, a clonal plant reproduction by seeds, is controlled in Paspalum spp. by a single locus which is blocked in terms of recombination. Partial sequence analysis of the apomixis locus revealed structural features of heterochromatin, namely the presence of repetitive elements, gene degeneration, and de-regulation. To test the epigenetic control of apomixis, a study on the distribution of cytosine methylation at the apomixis locus and the effect of artificial DNA demethylation on the mode of reproduction was undertaken in two apomictic Paspalum species. The 5-methylcytosine distribution in the apomixis-controlling genomic region was studied in P. simplex by methylation-sensitive restriction fragment length polymorphism (RFLP) analysis and in P. notatum by fluorescene in situ hybridization (FISH). The effect of DNA demethylation was studied on the mode of reproduction of P. simplex by progeny test analysis of apomictic plants treated with the demethylating agent 5'-azacytidine. A high level of cytosine methylation was detected at the apomixis-controlling genomic region in both species. By analysing a total of 374 open pollination progeny, it was found that artificial demethylation had little or no effect on apospory, whereas it induced a significant depression of parthenogenesis. The results suggested that factors controlling repression of parthenogenesis might be inactivated in apomictic Paspalum by DNA methylation.